2011
DOI: 10.1111/j.1755-148x.2011.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human endogenous retrovirus K is stimulated by ultraviolet radiation in melanoma

Abstract: Human endogenous retroviruses (HERVs) represent a cellular reservoir of potentially pathogenic retroviral genes. A growing body of evidence indicates that the activation of endogenous retroviral sequences might be involved in the transformation of melanocytes. In this study, we investigated the effects of ultraviolet radiation (UVR) on the expression of human endogenous retrovirus type K (HERV-K) in melanoma cells and non-melanoma cells in vitro. Solely in melanoma cell lines, irradiation with UVB (200 mJ/cm(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
0
37
1
Order By: Relevance
“…A recent study by Schmitt et al identified an HML-2 locus transcribed in melanomaderived samples only [118]. At the same time, it has been demonstrated that exposure to UV can activate HERVs, and HML-2 transcripts, in particular [118-120]. …”
Section: Transposable Elements and Ionizing Radiationmentioning
confidence: 99%
“…A recent study by Schmitt et al identified an HML-2 locus transcribed in melanomaderived samples only [118]. At the same time, it has been demonstrated that exposure to UV can activate HERVs, and HML-2 transcripts, in particular [118-120]. …”
Section: Transposable Elements and Ionizing Radiationmentioning
confidence: 99%
“…1). Since Tat has been shown to activate both viral and cellular genes (15,52,86,90,110), and since we observed that Jurkat-Tat cells have higher HERV-K (HML-2) gag RNA expression compared to the parental Jurkat counterpart, we hypothesized that the HIV-1 Tat protein might play a role in activating HERV-K (HML-2) expression during HIV-1 infection.…”
Section: Herv-k (Hml-2) Rna Expression Is Increased In Hiv-1-infectedmentioning
confidence: 99%
“…A possible role for HERV-K (HML-2) in pathogenesis has been considered in disorders such as systemic lupus erythematosus, rheumatoid arthritis, and neuroinflammation (3,36,43,53,77,90,112,113). Certain malignancies, most commonly germ cell tumors, melanoma, breast tumors, and prostate cancer, also show high levels of HERV-K (HML-2) antigen expression (18,59,62,104,110,132), sometimes accompanied by the production of viral particles (12,89), and yet the actual contribution of HERVs to disease remains to be characterized.…”
mentioning
confidence: 99%
“…25,41 Expression of HERV-K sequences in melanocytes and melanoma cells can be regulated by UVR. 33,43,44 Reiche et al 43 showed that after exposure to UVC, the expression of HERV-K was up-regulated in normal human epidermal melanocytes, but down-regulated or remained unchanged in melanoma cell lines. This study is consistent with a role, if any, of UVC and HERV-K in the initiation stage of melanoma development.…”
Section: Advances In Genomics Andmentioning
confidence: 99%
“…This study is consistent with a role, if any, of UVC and HERV-K in the initiation stage of melanoma development. Schanab et al 44 reported that irradiation with UVB resulted in a significant transcriptional activation of HERV-K POL and ENV genes, and induced the production of retroviral-like particles. Since the positive effects were not observed in benign melanocytes, this study supports a role of UVB in the malignant progression of melanoma cells.…”
Section: Advances In Genomics Andmentioning
confidence: 99%